Prova Brasil : a leitura em contexto de avaliação - análise e propostas - Bassiga, Leliane Fossaluza (2015)
The development of reading practice always causes uneasiness in the daily work of teachers. With regard to the Prova Brasil, this concern becomes more evident, because the student will be submitted to an evaluation which aims to diagnose their reading competence. Bearing in mind that, for the achievement of the evaluation said, there is a work in the classroom emphasizing the reading, it arises the questioning about how the reading has been explored in the questions of Prova Brasil and if these questions can help in the formation of a proficient reader. The present work analyzes the descriptors of the questions presented by the Caderno PDE (BRASIL, 2011), as a model for Prova Brasil from 5th grade of primary school, with regard to the treatment gave the reading. To the theoretical basis, this research was based on authors as Leffa (1996), Menegassi (1995), Geraldi (1997), Kleiman (2013) and Sole (1998), according to them, a proficient reader can be considered that one who is able to use various reading strategies to assist the process of understanding and interpretation of a text. Therefore, this work is guided in the interactional reading concept in their cognitive aspects. For the questions analysis, this research it is supported in the qualitative-interpretative methodology, since it analyses and explains the questions which involve the descriptors of Prova Brasil, in order to develop a work proposal with reading. With this analysis, we seek to ascertain whether the descriptors presented in the evaluation are in harmony with the questions that appeared in the guidelines for the Prova Brasil, in addition to raise the basic requirements for the formation of a proficient reader and analyze the justifications put forward by Caderno PDE (BRASIL, 2011) for the mistakes and successes of the students in the questions presented by the document. It was proved that some of the questions presented, with regard to the statements, are in disharmony with the skills provided by descriptors. For this reason, this research also presents a work suggestion from the reading strategies proposed by Sole (1998) and by Kleiman (2013), in order to propitiate a reading work more coherent with descriptors from Prova Brasil.